The social function of moral panic - Ilić Aleksandra (University of Belgrade - Faculty of Security Studies, Belgrade, 2020)
In this paper, the author discusses the social context of moral panic, ie the role of various social factors in the creation of moral panic. Starting from the known mechanisms of moral panic (traditional and newer), the author considers the roles of the subjects of informal and formal social control in this process. In that sense, it stands out the activity of various moral activists as representatives of the informal social structure who, by propagating the importance of moral protection, often participate in the process of creating of many moral panics. On the other hand, the activities of formal social control bodies are regulated by an appropriate legal frame-work whose task is to solve the problem of crime in society. This implies a professional attitude of the police, the prosecution and the courts in terms of combating crime. The author points out the problem of the participation of the representatives of these bodies in the creation and development of moral panic, considering it in the context of the culture of control, ie its elements, emphasizing especially the role of the police. The author connects all the mentioned segments of the social function of moral panic with the role of the media as an unavoidable factor in the process of moral panic. At the end of the paper, the author emphasizes the importance of the role of the media in raising awareness of the importance of individual actions of all social actors in order to avoid their participation in the creation of moral panic that unfavorable affects on solving the problem of crime.